Electrophysiological efficacy of temperature-controlled bipolar radiofrequency†. (1st February 2015) - Pozzoli, Alberto; Taramasso, Maurizio; Colombo, Daniele Filippo; Ancona, Francesco; Cianflone, Domenico; Bella, Paolo Della; Alfieri, Ottavio; Benussi, Stefano
Abstract: OBJECTIVE: Clinical success of atrial fibrillation (AF) ablation depends on persistent block of electrical conduction across the ablation lines. The fate of ablations performed with temperature-controlled bipolar radiofrequency (RF) is unknown. The purpose of this study was to validate the electrophysiological (EP) efficacy of these lesions, recording pulmonary vein isolation (PVI) after open chest ablation, in the human being. METHODS: Ten consecutive mitral patients (mean age: 53 ± 12 years) with concomitant AF were treated with the Cobra Revolution (Estech, San Ramon, CA, USA) bipolar RF device were enrolled for EP assessment. During surgery, pairs of additional temporary wires were positioned on the right PVs (RPV) and on the roof of the left atrium (RLA), before ablation. Pacing thresholds (PTs) were assessed before, after a single encircling ablation and at chest's closure. EP study was repeated before discharge and at 3 weeks. RLA wires served as control. RESULTS: Baseline PTs were 0.83 ± 0.81 mA (range 0.2–3 mA) from RPV and 1.13 ± 0.78 mA (range 0.3–3 mA) from RLA. PVI was reached in all patients acutely, and was maintained at 1 week. At 3 weeks, the PTs were 14.3 ± 4.3 mA from RPV (range 7–20 mA) and 3.1 ± 1.3 mA (range 1.5–7 mA) from RLA. All patients were discharged in sinus rhythm. CONCLUSIONS: Cobra Revolution temperature-controlled bipolar RF provides complete PVI after a single ablation up to 1 week. This notwithstanding, only 30% of patients were completely isolated (exit block validation) at 3 weeks.